2001
DOI: 10.1063/1.1351845
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and chemical passivation of hexagonal 6H–SiC surfaces by hydrogen termination

Abstract: Hydrogenation of 6H–SiC (0001) and (0001̄) is achieved by high-temperature hydrogen treatment. Both surfaces show a low-energy electron diffraction pattern representative of unreconstructed surfaces of extremely high crystallographic order. On SiC(0001), hydrogenation is confirmed by the observation of sharp Si–H stretching modes. The absence of surface band bending for n- and p-type samples is indicative of electronically passivated surfaces with densities of charged surface states in the gap of below 7×1010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
62
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 12 publications
4
62
1
Order By: Relevance
“…The second gap is caused by the coupling of the plasmon to the Si-H stretching vibration at the graphene/SiC interface. Consequently, ω + converges to 2090 cm −1 for high momentum transfers, while ω ++ converges to the Si-H stretching frequency of 2130 cm −1 for q → 0 which was previously observed by infrared absorption spectroscopy [19,33,34] where the momentum transfer is very small. Now we turn to the water intercalated sample [ fig.…”
supporting
confidence: 72%
“…The second gap is caused by the coupling of the plasmon to the Si-H stretching vibration at the graphene/SiC interface. Consequently, ω + converges to 2090 cm −1 for high momentum transfers, while ω ++ converges to the Si-H stretching frequency of 2130 cm −1 for q → 0 which was previously observed by infrared absorption spectroscopy [19,33,34] where the momentum transfer is very small. Now we turn to the water intercalated sample [ fig.…”
supporting
confidence: 72%
“…42,43 In previous studies 44 -48 we have investigated the chemical, electronic, and structural properties of 6H-SiC͕0001͖ surfaces that were hydrogenated by the method of Tsuchida et al The hydrogenated surfaces with (1ϫ1) periodicity were observed to be free of unwanted contaminations such as oxygen and hydrocarbons. 44 We were also able to show that the density of charged defects on SiC͑0001͒ can be pushed down to values of 7ϫ10 10 cm…”
Section: Introductionmentioning
confidence: 88%
“…Whereas the calculated Schottky barriers are referenced to the E VBM , the SiC substrates used in the experiments are n-type with the bulk Fermi level a few tenth of eV below the conduction band edge 22 . The use of E VBM as the reference is consistent with the freestanding nature of the transferred graphene and the Fermi level pinning within the SiC gap near the valence band edge 37 .…”
Section: Discussionmentioning
confidence: 99%
“…2b). This processing additionally leads to a chemically inert surface likely terminated with hydrogen or silicates 22,23 , which protects the SiC surface from oxidation during the transfer of graphene.…”
Section: Band Alignment Of Graphene and H-terminated Silicon Carbidementioning
confidence: 99%